Business Communication Strategies in Building A Positive Image Of Hospitals In The Era Of Healthcare Competition (Study at Djuansih Majalengka Hospital) - Nyoman Murtini (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
This study aims at analyze the business communication strategies implemented by Djuansih Hospital Majalengka in building a positive image amid the growing competition within Indonesia’s healthcare sector. The research employed a qualitative approach using a case study design, allowing an in- depth understanding of communication phenomena through participants’ perspectives within the organization’s natural context. Data were collected through in-depth interviews, participatory observations, and document analysis, involving hospital management, medical personnel, administrative staff, patients, and external partners. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014), consisting of data reduction, data display, and conclusion verification. The findings reveal that Djuansih Hospital’s business communication strategy is structured around three main pillars: (1) empathetic and human-centered communication, (2) integration of internal and external communication, and (3) optimization of digital media for reputation and public education purposes. Humanistic communication strengthens patient trust, while message integration ensures consistency between the desired and perceived hospital image. The effective use of digital channels such as websites, social media, and instant messaging platforms expands public engagement and enhances the hospital’s reputation as a modern, transparent, and responsive institution. Theoretically, this study enriches the literature on strategic business communication in healthcare by emphasizing the importance of communication integration across organizational levels. Practically, the results provide guidance for hospital management to design communication strategies grounded in empathy, transparency, and digital reputation. The study concludes that business communication is not merely a promotional tool but a strategic instrument for building trust and long-term loyalty within healthcare services.